Can Good Events Lead to Bad Outcomes? : Endogenous Banking Crises and Fiscal Policy Responses - Rochon, Celine (IMF Working Papers; Working Paper ;, 2006)
In this paper, we study the impact of labor market restructuring and foreign direct investment on the banking sector, using a dynamic general equilibrium model with a financial sector. Numerical simulations are performed using stylized Chinese data, and banks failures are generated through increases in the growth rate of the labor force, a revaluation of the exchange rate or an increase in debt issue to finance the government deficit, as compared to a benchmark scenario in which banks remain solvent. Thus bank failures can result from what might seem to be either beneficial economic trends, or correct monetary and fiscal policies. We introduce fiscal policies that modify relative factor prices by lowering the capital tax rate and increasing the tax rate on labor. Such policies can prevent banking failures by raising the return to capital. It is shown that such fiscal policies are, in the short run, welfare reducing.